(untitled) (Jurnal Ipteks Terapan, 2024)
Researchers want to know and analyze the use of digital marketing systems in increasing sales of MSMEs in Madina Regency. Data collection techniques were through questionnaires and interviews conducted by researchers with UMKN as research samples. The sampling technique in this research used a purposive sampling technique with a sample of 25 MSMEs. The research results show that MSMEs have utilized digital marketing systems in marketing their products. Understanding of MSME players is related to the digital marketing system, namely related to 96% of MSME players stating that they strongly agree with the ease of making digital payments, in running a business digitally, almost 92% of respondents stated that programmed promotional activities are needed, response to products between business actors and customers getting a response of 96% from MSMEs, of course this is related to suggestions and comments on the business, images of the products offered, information about the product, attractive product appearance and attractive and unique business design , getting a response of around 96%. So in managing a digital marketing system these strategies are needed in order to increase sales turnover.